2018
DOI: 10.1016/j.ecolind.2018.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Sounding out ecoacoustic metrics: Avian species richness is predicted by acoustic indices in temperate but not tropical habitats

Abstract: Affordable, autonomous recording devices facilitate large scale acoustic monitoring and Rapid Acoustic Survey is emerging as a cost-effective approach to ecological monitoring; the success of the approach rests on the development of computational methods by which biodiversity metrics can be automatically derived from remotely collected audio data. Dozens of indices have been proposed to date, but systematic validation against classical, in situ diversity measures are lacking. This study conducted the most comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
144
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(158 citation statements)
references
References 47 publications
10
144
2
2
Order By: Relevance
“…(Machado et al, 2017). The results of studies conducted at sites of varying degrees of degradation (from forests to agricultural land) in southeastern England and northwestern Ecuador showed that the greatest correlation (up to 65%) between acoustic indices and the number of bird species was observed in a temperate climate (Eldridge et al, 2018). However, the results of a number of studies failed to indicate a significant correlation of acoustic indices with the number of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Machado et al, 2017). The results of studies conducted at sites of varying degrees of degradation (from forests to agricultural land) in southeastern England and northwestern Ecuador showed that the greatest correlation (up to 65%) between acoustic indices and the number of bird species was observed in a temperate climate (Eldridge et al, 2018). However, the results of a number of studies failed to indicate a significant correlation of acoustic indices with the number of species.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of several acoustic parameters allowed to characterize and identify habitats with varying degrees of disturbance (mature forest, secondary growth and pasture) in Colombia (Gόmez et al, 2018) accurately predicted the diversity of birds in India (Buxton et al, 2018), etc. A multivariate analysis of the relative predictive power of acoustic indices shows that composite indices are more powerful predictors of bird species richness than any particular index (Eldridge et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Each of the above features was computed over 1 s of audio and concatenated to create a five-dimensional feature vector. This is referred to as a compound index in standard eco-acoustic studies 25 .…”
Section: Acoustic Feature Embeddingmentioning
confidence: 99%
“…entropy of the audio waveform 24 ) rather than a machine-learned, general acoustic fingerprint. Again, these indices can predict key ecological indicators in local contexts [25][26][27] , but they often fail to discriminate even large ecological gradients 28,29 , and behave unpredictably when transferred to new environments 30 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, acoustic indices have been widely used in ecological studies in highly pluvious tropical environments (e.g. Eldridge et al 2018;G omez et al 2018;Jorge et al 2018;Bradfer-Lawrence et al 2019). Although rainfall occurs seasonally in these environments, it can also vary unpredictably at small spatial and temporal scales (Poveda et al 2005;Rapp and Silma 2012).…”
Section: Introductionmentioning
confidence: 99%